2019
DOI: 10.1101/640086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Covalent Inhibitor of Gut Bacterial Bile Salt Hydrolases

Abstract: 17Bile salt hydrolase (BSH) enzymes are widely expressed by human gut bacteria and catalyze the 18 gateway reaction leading to secondary bile acid formation. Bile acids regulate key metabolic and 19 immune processes by binding to host receptors. There is an unmet need for a potent tool to 20 inhibit BSHs across all gut bacteria in order to study the effects of bile acids on host physiology. 21Here, we report the development of a covalent pan-inhibitor of gut bacterial BSH. From a 22 rationally designed candida… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 48 publications
(63 reference statements)
0
22
1
Order By: Relevance
“…Using a previously described assay of in vivo BSH activity 25 , we found that cecal BSH activity of CDAHFD-fed rats was significantly increased compared to control rats (Figure 5A). Importantly, no significant differences were seen in expression of BA synthesis or conjugation genes between CDAHFD-fed and control rats at 48 hours after dietary intervention (Figure S8).…”
Section: Bsh Inhibition By Aaa-10 Prevents Altered Intestinal Permeabmentioning
confidence: 87%
See 1 more Smart Citation
“…Using a previously described assay of in vivo BSH activity 25 , we found that cecal BSH activity of CDAHFD-fed rats was significantly increased compared to control rats (Figure 5A). Importantly, no significant differences were seen in expression of BA synthesis or conjugation genes between CDAHFD-fed and control rats at 48 hours after dietary intervention (Figure S8).…”
Section: Bsh Inhibition By Aaa-10 Prevents Altered Intestinal Permeabmentioning
confidence: 87%
“…400 µL of equimolar mixtures of bile acids at various concentrations to be tested were added to tubes and rotated overnight at BSH activity assay. BSH activity was quantified using a modified version of a previously described method 25 . Briefly, fresh cecal contents (approximately 20 mg) were diluted in PBS to obtain a concentration of mg/mL µM glycochenodeoxycholic acid-d4 (GCDCA-d4) was added to the mixture and incubated at 37ºC for 30 minutes, then frozen in dry ice for 5 minutes and stored at -80ºC until further analysis.…”
Section: Ethicsmentioning
confidence: 99%
“…In prior work, sulfonation of AAA-1 ( 1 ) at C3, a position that is exposed to solvent in the co-crystal structure of this compound with the BSH from the gut bacterium Bacteroides thetaiotaomicron ( B. theta ), increased the solubility of this compound and limited its systemic exposure. 24,28 The resultant compound AAA-2 , ( 2 ), however, was less potent than AAA-1 . 24 With the goal of improving potency while still maintaining gut restriction, we decided to append the optimized FMK warhead on naturally occurring bile acid cores found in both the murine and human gut (CDCA, DCA, ursodeoxycholic acid (UDCA), cholic acid (CA), and LCA).…”
Section: Resultsmentioning
confidence: 99%
“…24,28 The resultant compound AAA-2 , ( 2 ), however, was less potent than AAA-1 . 24 With the goal of improving potency while still maintaining gut restriction, we decided to append the optimized FMK warhead on naturally occurring bile acid cores found in both the murine and human gut (CDCA, DCA, ursodeoxycholic acid (UDCA), cholic acid (CA), and LCA). These compounds could then be sulfonated at the C3 position to produce second-generation inhibitor candidates (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation